Genetic predisposition to multiple myeloma at 5q15 is mediated by an ELL2 enhancer polymorphism - Li, Lily; Weinhold, Niels; Försti, Asta; Goldschmidt, Hartmut; Hemminki, Kari (Cell reports, 2017)
Summary - Multiple myeloma (MM) is a malignancy of plasma cells. Genome-wide association studies have shown that variation at 5q15 influences MM risk. Here, we have sought to decipher the causal variant at 5q15 and the mechanism by which it influences tumorigenesis. We show that rs6877329 G > C resides in a predicted enhancer element that physically interacts with the transcription start site of ELL2. The rs6877329-C risk allele is associated with reduced enhancer activity and lowered ELL2 expression. Since ELL2 is critical to the B cell differentiation process, reduced ELL2 expression is consistent with inherited genetic variation contributing to arrest of plasma cell development, facilitating MM clonal expansion. These data provide evidence for a biological mechanism underlying a hereditary risk of MM at 5q15.
Gesehen am 14.09.2018